Intestinal epithelial cell apoptosis and loss of barrier function in the setting of altered microbiota with enteral nutrient deprivation - Demehri, Farokh R.; Barrett, Meredith; Ralls, Matthew W.; Miyasaka, Eiichi A.; Feng, Yongjia; Teitelbaum, Daniel H. (Frontiers in Cellular and Infection Microbiology, 2013)
Total parenteral nutrition (TPN), a commonly used treatment for patients who cannot receive enteral nutrition, is associated with significant septic complications due in part to a loss of epithelial barrier function (EBF). While the underlying mechanisms of TPN-related epithelial changes are poorly understood, a mouse model of TPN-dependence has helped identify several contributing factors. Enteral deprivation leads to a shift in intestinal microbiota to predominantly Gram-negative Proteobacteria. This is associated with an increase in expression of proinflammatory cytokines within the mucosa, including interferon-γ and tumor necrosis factor-α. A concomitant loss of epithelial growth factors leads to a decrease in epithelial cell proliferation and increased apoptosis. The resulting loss of epithelial tight junction proteins contributes to EBF dysfunction. These mechanisms identify potential strategies of protecting against TPN-related complications, such as modification of luminal bacteria, blockade of proinflammatory cytokines, or growth factor replacement.